Evaluating the antimicrobial and anti-inflammatory mechanisms of dexmedetomidine in managing bone infection: a laboratory perspective - Merve Hayriye Kocaoğlu; Günseli Çubukçuoğlu Deniz; Duru Aras-Tosun; Evrim Güneş Altuntaş; Erkan Tuncay (BMC Musculoskeletal Disorders)
Abstract Background Osteomyelitis involves bone destruction, impaired bone formation, and systemic inflammation. Dexmedetomidine (DXMT) possesses antioxidant, anti-inflammatory, and anti-apoptotic properties alongside sedative and analgesic effects. This study evaluates DXMT's effects on markers of infection and bone healing using osteocyte-like cells infected by Staphylococcus aureus (S. aureus). Methods Human osteosarcoma-derived SAOS-2 cells were differentiated to an osteocyte-like phenotype over 28 days using potassium dihydrogen phosphate. Differentiation was verified via qPCR for osteogenic markers. Cytotoxicity of DXMT (0.1–10 µM) was tested using WST-1 assay and Reactive Oxygen Species (ROS) production analysis. Cells infected with S. aureus were treated with DXMT to assess its antimicrobial, anti-inflammatory (via ELISA for cytokines IL1-ß, TNF-⍺, IL-17, and IL-6), and osteogenesis-promoting effects. Results DXMT ≤ 1 µM did not affect cell viability, while 2, 5, and 10 µM DXMT administration reduced cell counts. A 5 µM dose slightly reduced intracellular bacterial load (6.2 log in controls vs. 6.1 log with DXMT), while neither less nor more DXMT was effective on reducing the S. aureus load. Doses ≥ 5 µM effectively reduced ROS production and inflammation post-infection in a time-dependent manner. S. aureus infection decreased osteogenic markers, but DXMT mitigated cellular stress and inflammation with a positive impact on osteogenesis at therapeutic doses. Conclusion DXMT at 5 µM is an optimal dose to reduce infection-induced cellular stress and promote bone healing in osteomyelitis in vitro, balancing antimicrobial effects and cytotoxicity.